2004
DOI: 10.1002/ajmg.c.30029
|View full text |Cite
|
Sign up to set email alerts
|

The keratins and their disorders

Abstract: Diseases caused by mutations in gene encoding keratin intermediate filaments (IF) are characterized by a loss of structural integrity in the cells expressing those keratins in vivo. This is manifested as cell fragility, compensatory epidermal hyperkeratosis, and keratin filament aggregation in some affected tissues. Keratin disorders are a novel molecular category including quite different phenotypes such as epidermolysis bullosa simplex (EBS), bullous congenital ichthyosiform erthroderma (BCIE), pachyonychia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 71 publications
3
35
0
Order By: Relevance
“…Cytokeratins form the intermediate filaments of the cytokeleton in epithelial cells. There are multiple so-called acidic and basic cytokeratins, and these form specific dimers that aggregate into filaments (48,49). Interestingly, keratin 4 and 13 are such a dimer, supporting the validity of our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Cytokeratins form the intermediate filaments of the cytokeleton in epithelial cells. There are multiple so-called acidic and basic cytokeratins, and these form specific dimers that aggregate into filaments (48,49). Interestingly, keratin 4 and 13 are such a dimer, supporting the validity of our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Histological analyses revealed that K5.Smad2 -/-tumors were generally poorly differentiated. The earliest K5.Smad2 -/-papillomas lacked stratified epithelial structure ( Figure 2C) and exhibited loss of loricrin and filaggrin, which are terminal differentiation markers (data not shown), and K1, an early differentiation marker ( Figure 2C), but expressed K8 ( Figure 2C), a marker of simple epithelia that is not expressed in stratified epithelia but is usually expressed in late-stage SCCs (20). In contrast, papillomas in WT mice showed partial or complete loss of loricrin and filaggrin (data not shown), without K8 expression, but retained uniform K1 expression (Figure 2C).…”
Section: Resultsmentioning
confidence: 96%
“…[21][22][23][24][25][26] In normal human epidermis, heterodimers of keratin 5 (K5) and K14 form the cytoskeleton of undifferentiated cells in the basal layer, which is replaced in suprabasal cells by K1 and K10, accompanied by K2 in the review review and KRT17. [28][29][30] Upon differentiation of keratinocytes, e.g., by raising the calcium level with or without the addition of growth factors (EGF and fibroblast growth factor-10) or adding the EGF-receptor inhibitor PD153035, expression of the differentiation-related keratins K1 and K10 are induced in a subpopulation of cells.…”
Section: Keratin Expression In Normal Human Skin and Cultured Keratinmentioning
confidence: 99%